Pharmacologically screened aphrodisiac plant-A review of current scientific literature - Patel D.K.; Kumar R.; Prasad S.K.; Hemalatha S. (My University, 2025)
Substances which are used to treat sexual dysfunction or to improve sexual behavior and satisfaction in humans and animals are called 'aphrodisiac'. Uses of plant material to treat sexual disorder is a long back history in the different system of medicine and it was practiced by different type of vaidyas and traditional healer in almost all the countries in the world, like China, India, Egypt, Rome and Greek. Even though there was an unavailability of the scientific data, these substances have been used as aphrodisiac. During the historic times Lytta vesicatoria, Tribulus terrestris, Ptychopetalum olacoides, Crocus sativus, Bufo marinus, Myristica fragrans, Theobroma cocao and other plants have been investigated for its aphrodisiac activity by in vivo and in vitro model. Even though the study showed positive response to a particular substance, there is always a need to run the clinical trial before administering the tested drug in human being. The present review article summarizes the plant material which has been tested for its aphrodisiac activity in different experimental model (in vitro, in vivo on animal models, or in human clinical trials) and comply its claim in the different system of medicine. A brief overview about the data of percentage study in the last eighteen years duration on aphrodisiac activity of plant material was done on the basis of the CAB abstract database.